Prenatal vitamin D3 supplementation suppresses LL-37 peptide expression in ex vivo activated neonatal macrophages but not their killing capacity. Issue 6 (28th September 2014) - Raqib, Rubhana; Ly, Anna; Akhtar, Evana; Mily, Akhirunnesa; Perumal, Nandita; Al-Mahmud, Abdullah; Rekha, Rokeya Sultana; Baqui, Abdullah Hel; Roth, Daniel E.
<x content-type="archive" xml:space="preserve">Abstract</x> Vitamin D has regulatory effects on innate immunity. In the present study, we aimed to assess the effect of prenatal vitamin D3 (vitD3) supplementation on neonatal innate immunity in a randomised, placebo-controlled trial by evaluating cathelicidin (LL-37) expression and the killing capacity of macrophages. Healthy pregnant women (n 129) attending a clinic in Dhaka were randomised to receive either a weekly oral dose of 0·875 mg vitD3 or placebo starting from 26 weeks of gestation up to delivery. Serum, plasma and monocyte-derived macrophages (MDM) were obtained from the cord blood. 25-Hydroxyvitamin D (25(OH)D) concentration was measured in serum. MDM were stimulated with or without Toll-like-receptor 4 ligand (TLR4L). Innate immune function was assessed by measuring LL-37 peptide levels in the culture supernatant of MDM by ELISA, LL-37 transcript levels by quantitative PCR, and ex vivo bactericidal capacity of MDM. vitD3 supplementation did not increase LL-37 peptide levels in plasma or in the extracellular fluid of macrophages with or without TLR4L induction. However, stimulated intracellular LL-37 expression (ratio of stimulated:unstimulated MDM) was significantly reduced in the vitamin D group v. placebo (P= 0·02). Multivariate-adjusted analyses showed that intracellular LL-37 peptide concentration from stimulated MDM was inversely associated with 25(OH)D concentration in serum (P= 0·03). TLR4L stimulation increased the bactericidal capacity of MDM compared with the unstimulated ones (P= 0·01); however, there was no difference in killing capacity between the two groups. A weekly dose of 0·875 mg vitD3 to healthy pregnant women suppressed the intracellular LL-37 peptide stores of activated macrophages, but did not significantly affect the ex vivo bactericidal capacity of cord blood MDM.